Impacts of land-use and management histories of maize fields on the structure, composition, and metabolic potentials of microbial communities - Chinenyenwa Fortune Chukwuneme (Elsevier, 2021)
Microbial diversity and functionality are impacted by land-use and management practices, with studies reporting reduced microbial activities due to anthropogenic activities. In this study, we analyzed and compared the composition, diversity, and metabolic profiles of microbial communities in maize rhizosphere soils of a former grassland and an intensively cultivated land. Metagenomic DNA was extracted from maize rhizosphere and bulk samples and sequencing was performed using the shotgun metagenomic approach. Comparative analyses of the metagenomes revealed differences in the distribution of microbial communities across the soils. Alpha diversity indices (Simpson, Shannon, and Evenness) were higher in the former grassland soils and beta diversity analysis revealed a significant difference (p = 0.01) in microbial community structure between the fields, with the highest dissimilarity (21.03%) observed between the rhizosphere soils. Among all taxonomic levels in the study, a total of 23 taxa were observed to be differentially abundant in the samples. Soil pH, with a contribution of 51% and a p-value of 0.002 was the most influential soil parameter that determined microbial distribution across the soils. Differences were also observed in the abundance of metabolic pathways (alpha = 0.05) across the samples. Overall, differences in the soils’ chemical properties were attributed to land-use and management histories, which contributed to the dissimilarities observed in the microbial structural diversity and metabolic pathways. These results provide knowledge on the impact of land-use practices on microbial diversity and function in cultivated soils and create opportunities for future experiments to mine the unclassified bacteria/sequences, with the intention of discovering novel microbes of agricultural importance.